Quality of life of renal transplant donors - Sagar Koirala (Society of Surgeons of Nepal, 2017)
Introduction: End stage renal disease has a high rate of mortality and morbidity. Kidney transplantation remains the best treatment option in comparison to other forms of renal replacement therapy. Live related donor renal transplantation was started at TUTH in 2008. Compared to other established centers, the outcome of transplantation was comparable. Though there is considerable evidence showing that donors are able to return to their healthy life, quality of life (QOL) assessment using standardized questionnaires has not yet been done in our centre. This study was carried out in order to compare QOL before and after donor nephrectomy.